2022
DOI: 10.1038/s42004-022-00640-4
|View full text |Cite
|
Sign up to set email alerts
|

Reading and erasing of the phosphonium analogue of trimethyllysine by epigenetic proteins

Abstract: Nε-Methylation of lysine residues in histones plays an essential role in the regulation of eukaryotic transcription. The ‘highest’ methylation mark, Nε-trimethyllysine, is specifically recognised by Nε-trimethyllysine binding ‘reader’ domains, and undergoes demethylation, as catalysed by 2-oxoglutarate dependent JmjC oxygenases. We report studies on the recognition of the closest positively charged Nε-trimethyllysine analogue, i.e. its trimethylphosphonium derivative (KPme3), by Nε-trimethyllysine histone bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…6B, Phosphonium). 83 In another study, we demonstrated the need for L-stereochemistry for efficient lysine demethylation by KDMs. 67 However, KDMs were observed to be more accepting towards conformationally constrained lysine analogues, with demethylation being catalysed by KDM4 subfamily members for trans-C-4/C-5 dehydrolysine substrates (K E me2) (Fig.…”
Section: Lysine Demethylasesmentioning
confidence: 92%
See 1 more Smart Citation
“…6B, Phosphonium). 83 In another study, we demonstrated the need for L-stereochemistry for efficient lysine demethylation by KDMs. 67 However, KDMs were observed to be more accepting towards conformationally constrained lysine analogues, with demethylation being catalysed by KDM4 subfamily members for trans-C-4/C-5 dehydrolysine substrates (K E me2) (Fig.…”
Section: Lysine Demethylasesmentioning
confidence: 92%
“…5C, Phosphonium). 83 Increased binding affinities were observed for H3K P 4me3-reader complexes, indicating that it is possible that unnatural Kme3 mimics associate stronger with reader proteins.…”
Section: Lysine Methylation Readersmentioning
confidence: 99%
“…Peptide synthesis and purification : Peptides derived from TRPA1, TRPV3 and the 1CA consensus sequence [28] were synthesised with C‐terminal amides using a CEM Liberty Blue solid‐phase peptide synthesis (SPPS) machine using Oxyma®/DIC‐mediated, microwave‐assisted couplings as reported [43] . In brief, SPPS was performed using rink amide MBHA resin and 0.2 M solutions of FMOC‐protected amino acids in DMF.…”
Section: Methodsmentioning
confidence: 99%
“…11–13 Comparative binding analysis demonstrated a selectivity trend for higher methylation states (Kme3 > Kme2 > Kme > K) and for l -Kme3 over d -Kme3. 9,14 In addition, H3K4me3 readers have shown affinity towards cysteine-derived analogues of Kme3 in histone peptides and intact histone proteins, 15–18 and bind the simplest neutral carba analogue, 12 the positively charged phospha analogue, 19 and trimethyllysine analogues that differ in the length of the side chain. 20,21…”
mentioning
confidence: 99%
“…[11][12][13] Comparative binding analysis demonstrated a selectivity trend for higher methylation states (Kme3 4 Kme2 4 Kme 4 K) and for L-Kme3 over D-Kme3. 9,14 In addition, H3K4me3 readers have shown affinity towards cysteine-derived analogues of Kme3 in histone peptides and intact histone proteins, [15][16][17][18] and bind the simplest neutral carba analogue, 12 the positively charged phospha analogue, 19 and trimethyllysine analogues that differ in the length of the side chain. 20,21 The backbone of the H3K4me3-containing histone tail assumes unstructured conformations in an unbound state, and is subjected to induced-fit conformational transitions to mediate intramolecular hydrogen-bonding, cation-p interactions and salt-bridges with the reader domain (Fig.…”
mentioning
confidence: 99%